Fibromyalgia and arthritides - A. Alciati; R. Casale; M. Di Franco; M. Benucci; S. Sallì; F. Atzeni; P. Sarzi-Puttini (PAGEPress Publications, 2012)
Fibromyalgia (FM) is a chronic pain syndrome that affects at least 2% of the adult population. It is characterised by widespread pain, fatigue, sleep alterations and distress, and emerging evidence suggests a central nervous system (CNS) malfunction that increases pain transmission and perception. FM is often associated with other diseases that act as confounding and aggravating factors, such as rheumatoid arthritis (RA), spondyloarthritides (SpA), osteoarthritis (OA) and thyroid disease. Mechanism-based FM management should consider both peripheral and central pain, including effects due to cerebral input and that come from the descending inhibitory pathways. Rheumatologists should be able to distinguish primary and secondary FM, and need new guidelines and instruments to avoid making mistakes, bearing in mind that the diffuse pain of arthritides compromises the patients' quality of life.